2018
DOI: 10.48048/wjst.2019.6292
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Antibacterial Hydrogel Sheet Dressings Composed of Poly(vinyl alcohol) and Silk Fibroin for Wound Healing Application

Abstract: Hydrogels are soft materials that contain high water content within their 3-dimensional structure. Such extremely hydrated environment allows hydrogels to recapitulate the structure of many native tissues inside the body. In biomedical application, hydrogels have been extensively used as biocompatible materials, drug delivery systems, and tissue-engineered scaffolds that can be designed to possess either permanent or slow-degradation properties. In this research, we applied gamma irradiation to develop transpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…To this end, crosslinking by the use of high energy radiation such as gamma or electron beam provides an alternative platform to fabricate hydrogels at relatively mild conditions without the use of harmful chemical reagents [1][2][3]. Previous studies also showed that gamma irradiation could be used to effectively process cytocompatible PVAbased hydrogels containing silk fibroin [4] or silk sericin [23]. Therefore, these cytocompatibility results of bare hydrogel sheets approve both the materials and processing method, providing an important 1 st step to warrant a further biological evaluation in an animal model such as wound healing efficacy, or skin irritation patch test in a clinical trial.…”
Section: Cytocompatibility Evaluation Of Bare Hydrogel Sheets By Extr...mentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, crosslinking by the use of high energy radiation such as gamma or electron beam provides an alternative platform to fabricate hydrogels at relatively mild conditions without the use of harmful chemical reagents [1][2][3]. Previous studies also showed that gamma irradiation could be used to effectively process cytocompatible PVAbased hydrogels containing silk fibroin [4] or silk sericin [23]. Therefore, these cytocompatibility results of bare hydrogel sheets approve both the materials and processing method, providing an important 1 st step to warrant a further biological evaluation in an animal model such as wound healing efficacy, or skin irritation patch test in a clinical trial.…”
Section: Cytocompatibility Evaluation Of Bare Hydrogel Sheets By Extr...mentioning
confidence: 99%
“…The soft consistency of hydrogels enables them to mimic the structure of natural tissue and make them an attractive candidate for a wide range of biomedical applications including contact lenses, wound dressings, drug delivery systems and hygiene products [2,3]. In terms of wound dressings, hydrogels in the form of flat sheets or filler strands can be used as a protective barrier over skin lesions to absorb wound exudate and provide the appropriate moist environment that promotes natural wound healing [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…We then tested if such repeated irradiation would affect the swelling and mechanical properties of the hydrogels. Previously, we demonstrated that both the gel strength and tensile strength of the hydrogel sheets increased with the irradiation doses used to crosslink the hydrogels having the similar 10% (w/v) PVA system and gamma doses ranging from 25 to 80 kGy [26]. Therefore, based on our current data on swelling, hydrogel sheets that formed at 25 and 40 kGy were selected for the repeated irradiation experiments, as the swelling became saturated at higher doses.…”
Section: Effect Of Repeated Irradiation On the Sterility Swelling And...mentioning
confidence: 97%
“…Round hydrogel sheets from the 5.5 cm dishes were first rinsed with DI water to remove unreacted PVA. The samples were then fully immersed for 24 h in an aqueous solution containing 142 mmol NaCl and 2.5 mM CaCl 2 , which simulated the discharge at the wound site [26], before being dried at 60 • C to a constant weight. The equilibrium degree of the swelling was calculated as follows:…”
Section: Hydrogel Characterization 431 Swellingmentioning
confidence: 99%